Morus alba derived Kuwanon‐A combined with 5‐fluorouracil reduce tumor progression via synergistic activation of GADD153 in gastric cancer. Issue 1 (19th February 2023) - Su, Jingjing; Thakur, Abhimanyu; Pan, Guangzhao; Yan, Jianglong; Gaurav, Isha; Thakur, Sudha; Yang, Zhijun; Cili, Alma; Zhang, Kui
Abstract: Despite the application of conventional strategies including chemotherapy, radiotherapy, surgery, or immunotherapy, the mortality of gastric cancer (GC) patients remains high. Often, GC is not diagnosed until it has reached late stage, resulting in a missed surgical window. Therefore, a new therapeutic intervention for GC is necessary. Here, the combined application of Kuwanon‐A (KA) and 5‐fluorouracil (5‐FU) was evaluated for its potential to combat GC for the first time. To determine the anticancer activity of KA (from Morus alba ) along with 5‐FU against GC, and their mechanism via GADD153, we examained anticancer potential of KA along with 5‐FU via in vitro assays with GC cells, namely MKN‐45, SGC‐7901, HGC‐27, and BGC‐823, and in vivo assays with mouse xenograft of GC. KA alone could induce G2/M phase arrest and apoptosis in GC cells by activating GADD153 through the PERK/elF2α/ATF4 and IRE1/XBP1 signaling pathways, suggesting a critical role of increased endoplasmic reticulum stress in KA‐induced apoptosis of GC cells. Moreover, the combination of KA and 5‐FU showed an enhanced synergistic anticancer effect against GC both in vitro and in vivo. Conclusively, the combination of KA and 5‐FU can act as an effective anticancer regimen in combating GC. Abstract : Kuwanon‐A (KA) induced G2/M arrest and apoptosis in gastric cancer (GC) cells via GADD153‐PERK/elF2α/ATF4 & IRE1/XBP1 pathways, highlighting ER stress's role in KA‐induced apoptosis. KA along with 5‐fluorouracil (5‐FU) augmented antitumor effect against GC both in vitro and in vivo.